Os artifícios do Estado para a reprodução do capital : o discurso do “comércio justo” - Reis, Leandro Cavalcanti (2015)
This thesis aims entitled The State of devices for the reproduction of capital: the discourse of "fair trade" aimed to analyze the functionality of the "fair trade" in the capital accumulation process, from the reality of PRITAM company, located in Submédio São Franciscano, located in Casa Nova-BA. We start the following questions: the "fair trade" is an alternative to the capital or business relationship meets the logic of accumulation by dispossession? This form of production guarantees rural workers better conditions of life and work? A search of the preposition adopted the dialectical historical materialism which ensures that the analysis of reality is considered in its entirety, in an interdependent phenomena, and multideterminações. In this sense, theoretical readings reflective been developed on the exploitation of the labor force in the countryside, monopolization and territorial planning, state functionality to capital and "fair trade" in the capital of the globalization context. It was found that there is a wide spread of speeches claiming that the "fair trade" is an important means of addressing the socio-spatial inequalities, and that this form of business relationship will be a just society. That thought has gained strength in several groups (social movements, political parties, intellectuals, including geographers) and is part of the state policies. In all its particular forms of information or advertising, publicity or direct entertainment consumption, the spectacle is the present model of socially dominant life. It is the omnipresent affirmation of the choice already made in production and its corollary - the consumer. Thus, it was possible to identify the limits of "fair trade". In addressing the capital-labor struggle, the company uses the label to enter another market position, moving from a commodity market to a niche market that rather than work as a strategy to combat the exploitation of labor in the field , has served as a way to ensure the extraction of rent of land.